Enzymatic production of protein hydrolysates from steelhead (Oncorhynchus mykiss) skin gelatin as inhibitors of dipeptidyl-peptidase IV and angiotensin-I converting enzyme. (January 2017) - Cheung, Imelda W.Y.; Li-Chan, Eunice C.Y.
Highlights: Gelatin hydrolysates with ACE and DPP-IV inhibitory activity were produced. Bioactivity was enhanced by either ultrafiltration or sequential enzyme hydrolysis. The <3 kDa fraction of hydrolysates produced by pepsin, Corolase®N or papain showed strong ACE and DPP-IV inhibition. ACE inhibitory activity of some hydrolysates improved after second hydrolysis with CorolaseN. Hydrolysis with papain followed by either ultrafiltration or CorolaseN yielded strong dual bioactivity. Abstract: The objective of this study was to generate protein hydrolysates with dual in vitro inhibitory activities against dipeptidyl-peptidase IV (DPP-IV) and angiotensin-I converting enzyme (ACE), by proteolytic enzymes acting either individually or sequentially on steelhead skin gelatin. The results showed strong dual bioactivity in the low molecular weight (<3 kDa) fractions obtained by ultrafiltration of hydrolysates produced using the enzymes pepsin, CorolaseN or papain. Alternatively, unfractionated hydrolysates exhibiting high ACE and DPP-IV inhibitory activities as well as yields could be attained by strategic selection of two enzymes for successive hydrolysis of gelatin. In particular, hydrolysates produced using 4% papain for 2 h followed either by ultrafiltration or by a second hydrolysis with 1% CorolaseN for 2 h, presented potent dual activity as ACE and DPP-IV inhibitors, and should be investigated further as potential functional food ingredients or nutraceuticals for the management of hypertension and diabetes.